Development and Evaluation of a Questionnaire to Document Worker Exposures to Mechanical Loading at a Workplace Level. Issue 1 (2nd January 2016) - Yazdani, Amin; Bigelow, Philip; Carlan, Niki; Naqvi, Syed; Robson, Lynda S.; Steenstra, Ivan; McMillan, Keith; Wells, Richard
Abstract : OCCUPATIONAL APPLICATIONS Despite many biomechanical risk factors being clearly linked to the development of musculoskeletal disorders, little measurement of the prevalence of physical loads in workplaces is being conducted. Through a collaborative partnership with unions, a health and safety organization, and researchers, this project developed and tested a questionnaire to document exposures to physical workloads in workplaces. Surveys were first completed independently by two members of each organization's joint health and safety committee. The same survey was later completed collectively to arrive at a consensus between the two members. Results of the surveys were then compared to findings from a walk-through conducted by an ergonomist. Substantial to excellent agreement was found between the identification and assessment of exposure levels to 26 types of physical loading by the ergonomist and workplace. Such a survey could be an efficient technique to characterize the loads to which workers are exposed. Such data could have value for targeting prevention activities at a workplace or jurisdictional level.TECHNICAL ABSTRACT Background : The presence and level of exposure to mechanical risk factors can be considered leading indicators in the development of musculoskeletal disorders. Although there are multiple methods for musculoskeletal disorder risk assessment, most of these methods record data related to an individual person performing a specific task. Rather in this questionnaire, we are collecting the exposure data at the workplace level (i.e., for all people experiencing this type of load). Purpose : The aim of this study was to develop and test a survey to document the presence and levels of multiple types of physical loading in a workplace. Methods : A survey requesting information on exposure to 26 types of loading was developed. It was distributed to management and worker representatives for their individual and then their consensus ratings. The same survey was completed by an ergonomist during a site visit. Results : Complete data sets were obtained from 30 workplaces across a variety of sectors. The most prevalent loads reported were sitting, neck bent or twisted, computer use, and carrying loads. For the presence or absence of specific loads, the consensus and ergonomist's ratings agreed well with over 90% for nine of 26 load types and over 70% agreement for 10 other load types. For a calculated exposure index, only four load types differed significantly across the two types of raters. Conclusions : The study demonstrates that a survey completed by individuals familiar with the workplace could be used to document exposure to physical loading at a workplace level in an efficient manner. Such a survey may be useful in understanding the nature and prevalence of such exposures and targeting prevention activities at a workplace or jurisdictional level.